Clojure data analysis cookbook : over 110 recipes to help you dive into the world of practical data analysis using Clojure - Rochester, Eric (Packt Publishing, 2013)
Full of practical tips, the ""Clojure Data Analysis Cookbook"" will help you fully utilize your data through a series of step-by-step, real world recipes covering every aspect of data analysis. Prior experience with Clojure and data analysis techniques and workflows will be beneficial, but not essential